2014
DOI: 10.5114/cipp.2014.47447
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity, dimensionality and factorial invariance of the Rosenberg Self-Esteem Scale: a bifactor modelling approach among children of prisoners

Abstract: background The Rosenberg Self-Esteem Scale (RSES) has traditionally been conceptualised as a unidimensional measure of self-esteem, but empirical evidence is equivocal, with some studies supporting a one-factor solution and others favouring multidimensional models. participants and procedureThe aim of this study was to examine the factor structure, factorial invariance and composite reliability of the RSES within a European sample of children affected by parental imprisonment (N = 724). The study specified and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…One approach to addressing that question is to use a bifactor structural representation where the general factor represents the substantive trait and the group factors represent method artifacts associated with item wording (see Hyland, Boduszek, Dhingra, Shevlin, & Egan, 2014; McKay, Boduszek, & Harvey, 2014; Sharratt, Boduszek, Jones, & Gallagher, 2014). These studies suggest that the RSES is essentially unidimensional once controlling for the effects of direction of wording (e.g., Donnellan, Ackerman, & Brecheen, 2016); moreover, problems appear localized to the negatively-worded items (Corwyn, 2000; Marsh, 1996).…”
Section: The Structure Of the Rosenberg Self-esteem Scale (Rses)mentioning
confidence: 99%
“…One approach to addressing that question is to use a bifactor structural representation where the general factor represents the substantive trait and the group factors represent method artifacts associated with item wording (see Hyland, Boduszek, Dhingra, Shevlin, & Egan, 2014; McKay, Boduszek, & Harvey, 2014; Sharratt, Boduszek, Jones, & Gallagher, 2014). These studies suggest that the RSES is essentially unidimensional once controlling for the effects of direction of wording (e.g., Donnellan, Ackerman, & Brecheen, 2016); moreover, problems appear localized to the negatively-worded items (Corwyn, 2000; Marsh, 1996).…”
Section: The Structure Of the Rosenberg Self-esteem Scale (Rses)mentioning
confidence: 99%
“…Recent debate is centred on its use as an all-inclusive construct or as a twofold variable scheme. The studies of Debowska et al (2017), Sharratt et al (2014), Boduszek et al (2013), and Boduszek et al (2012) suggest that the twofold structure is a more appropriate manner of applying RSES in social studies. Recent research applying the bifactorial modelling also confirmed the two-dimensional nature of the self-esteem construct (Hyland et al 2014;McKay et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Rosenberg Self-esteem Scale (SES) adapted by Dzwonkowska, Lachowicz-Tabaczek and Łaguna (2008) measures global self-esteem in adolescents and adults (Sharratt, Boduszek, Jones, & Gallagher, 2014). The reliability of the Polish adaptation measured with Cronbach's α for different standardization groups -as well as for the entire sample -ranges between .81 and .83.…”
Section: Rosenberg Self-esteem Scale (Ses)mentioning
confidence: 99%